2015
DOI: 10.3109/00016489.2015.1110750
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hearing loss and vestibular dysfunction in patients with sudden sensorineural hearing loss

Abstract: SSHL patients with vertigo or abnormal caloric test displayed worse hearing loss; and vice versa, vertigo and abnormal caloric results happened more frequently in SSHL patients with profound hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1
7

Year Published

2017
2017
2106
2106

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 16 publications
3
40
1
7
Order By: Relevance
“…In the present study, out of 71 patients, 12 (17%) patients reported bilateral hearing loss (Pure Tone Average greater than 25dB HL) of various degrees. Vertigo is associated with hearing loss in patients with sudden sensorineural hearing loss 12 . Twelve patients out of 71 patients had unilateral hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, out of 71 patients, 12 (17%) patients reported bilateral hearing loss (Pure Tone Average greater than 25dB HL) of various degrees. Vertigo is associated with hearing loss in patients with sudden sensorineural hearing loss 12 . Twelve patients out of 71 patients had unilateral hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…2 A comprehensive evaluation of the extent of the vestibular lesions involved in MPSHL may be useful to understand the range and extent of inner ear lesions, and provide some tips on the potential pathogenesis. 3 In recent years, there has been a growing awareness of vestibular dysfunction in people with hearing loss (HL). The cervical vestibular-evoked myogenic potentials (cVEMPs) is an objective and non-invasive test, which allows the rating of saccular function and lower vestibular nerve.…”
Section: Introductionmentioning
confidence: 99%
“…[1,4,5,12] Some reports have indicated that abnormal caloric test results in SSNHL patients may be of negative prognostic value [1,13], whereas other studies have shown that the results of caloric testing may not be predictive of SSNHL [4,5,14]. Furthermore, several recent studies have included the VEMP test in the evaluation of patients with SSNHL, for whom abnormal results of vestibular examinations were associated with profound hearing loss [6,15]. 5 The present study aimed to determine the association of VFT results with the initial disease severity and prognosis of hearing outcomes in SSNHL patients.…”
Section: Introductionmentioning
confidence: 99%